Aerodynamic characteristics of trains on a viaduct with non-uniform cross-section under crosswinds by wind tunnel tests. Issue 9 (July 2021) - Yu, Kehui; He, Xuhui; Cai, Chenzhi; Yan, Lei; Zou, Yunfeng
This paper focuses on the aerodynamic characteristics of trains on a non-uniform double-track railway bridge under crosswinds through a scaled 1:40 sectional model wind tunnel test. Pressure measurements of five cross-sections of two types of trains, one with round roof and one with blunt roof, at the upstream and downstream tracks of the bridge were conducted under crosswinds with wind attack angles between −12° and 12°. The mean wind speed and turbulence intensity profiles around the windward surface of the train in the downwind and upward directions were also measured using cobra probe to obtain the boundary layer above the bridge surface. The results show that the shapes of train and bridge, as well as the wind attack angle, affect the aerodynamic characteristic of the train on the non-uniform bridge girder. The mean and fluctuating pressure coefficients are similar for all five cross-sections of the trains while the train is at the upstream track. However, when the train is at the downstream track, the extreme mean and fluctuating pressure coefficients around the windward and top surfaces of each cross-section on the train are different. At the downstream track, the mean wind speed profile and the turbulence intensity profile around the top of the train vary dramatically due to the separation flow caused by the leading edge of the bridge girder.